ENVIRONMENTAL, SOCIAL, AND GOVERNANCE IN FINANCIAL STATEMENT ANALYSIS: BIBLIOMETRIC PERSPECTIVES - Gregorius Jeandry; Zainuddin Zainuddin; Amin Dara; Iqbal M Aris Ali; Muhammad Ali Ahmad (EKUITAS (Jurnal Ekonomi dan Keuangan), 2026)
This study aims to examine the development and integration of Environmental, Social, and Governance (ESG) into financial statement analysis using a hybrid approach that combines bibliometric analysis and a Systematic Literature Review (SLR). The study analyzes Scopus-indexed journal articles published between 2015 and 2025 to map publication trends, dominant themes, the intellectual structure, and the evolving direction of ESG research. The findings reveal that ESG research has grown significantly and become increasingly integrated into mainstream accounting and finance literature. The major research themes include ESG reporting, non-financial disclosure, IFRS, assurance, risk management, and corporate value creation. The SLR findings indicate that ESG is no longer regarded as supplementary information but has evolved into an analytical dimension that enhances the assessment of corporate performance, risk, reporting quality, and sustainability. ESG integration is driven by regulatory pressure, reporting standardization, governance quality, information credibility, and the growing demand from stakeholders for transparent information. This study contributes conceptually by emphasizing the importance of an integrated financial statement analysis framework that combines financial and non-financial information to support higher-quality decision-making.